The effects of skin tone, height, and gender on earnings - Devaraj, Srikant (PLoS One, 2018)
Using a theoretical approach grounded in implicit bias and stereotyping theories, this study examines the relationship between observable physical characteristics (skin tone, height, and gender) and earnings, as measured by income. Combining separate streams of research on the influence of these three characteristics, we draw from a sample of 31,356 individual-year observations across 4,340 individuals from the National Longitudinal Study of Youth (NLSY) 1997. We find that skin tone, height, and gender interact such that taller males with darker skin tone attain lower earnings; those educated beyond high school, endowed with higher cognitive ability, and at the higher income level (>75(th) percentile) had even lower levels of earnings relative to individuals with lighter skin tone. The findings have implications for implicit bias theories, stereotyping, and the human capital literature within the fields of management, applied psychology, and economics.